The Evolution of Islamic Political and Intellectual Centers: From Baghdad to Istanbul: A Study of Medieval Islamic Civilization - Muzaiyana, Muzaiyana (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
This article critically revisits the historical trajectory of the political and intellectual centers of Islamic civilization during the Medieval period, with a particular focus on the transition from Baghdad’s intellectual preeminence to Istanbul’s emergence as the center of political power. It aims to explore how Islamic political structures and scholarly traditions transformed and adapted in response to the sociopolitical and geographical dynamics between the 8th and 13th centuries CE.Using a historical-qualitative method through library research, the study reveals that under the leadership of Caliphs Harun al-Rashid and al-Ma’mun, Baghdad thrived as a global center of knowledge through the establishment of the Bayt al-Hikmah (House of Wisdom). Extensive efforts to translate Greek philosophical and scientific texts greatly advanced intellectual development in areas such as philosophy, mathematics, astronomy, medicine, and biology.However, the Mongol invasion in 1258 CE brought about the collapse of Abbasid authority and a decentralization of power, paving the way for Istanbul to rise as the new center of Islamic political and cultural life under the Ottomans. This historical shift underscores that the preservation and evolution of intellectual traditions—alongside adaptability to historical change—were just as vital as military strength in shaping the trajectory of Islamic civilization.